(untitled) (Actualité en allergologie et en immunologie au Canada, 2024)
Secondary hypogammaglobulinemia (SHG) is characterized by reduced immunoglobulin levels due to extrinsic causes, such as a medication or an acquired disease process, resulting in decreased immunoglobulin production or increased immunoglobulin loss. Most published reports of SHG refer to IgG hypogammaglobulinemia and data on isolated IgA or IgM hypogammaglobulinemia is limited. The common causes of SHG include medications, hematological malignancies, and conditions associated with protein loss. Hypogammaglobulinemia can increase the risk of infection, morbidity and mortality, particularly in patients who may already be immunocompromised due to their associated condition or use of immunosuppressive therapies. With growing use of immunosuppressive or immunomodulatory treatments that affect B-cells, it is increasingly important to assess and monitor for SHG. Treatment of the underlying condition or removal of the extrinsic factor often results in resolution of the SHG. A subset of patients presenting with autoimmune or malignant conditions can have a primary immunodeficiency (PID) or primary immune regulatory disorder. It is therefore important to consider both primary and secondary causes when assessing hypogammaglobulinemia. This article will review these common causes and discuss an approach to assessment and management of SHG.